How Layers of Context and Material Deprivation Impact Reemployment in Stable or Casual Work - Rodwell, John; Flower, Rebecca (My University, 2023)
Reemployment for those who are unemployed is both economically and socially important but may be constrained because of the person’s context. The current study investigates key socioeconomic, structural, and individual factors that may impact the likelihood of reemployment for unemployed working age adults over the period of a year. Reemployment is further separated in terms of stability and security by delineating casual versus non-casual reemployment. A multinomial regression analysis of an Australian dataset (n = 375 adults who reported no limitation to their ability to gain employment) found that economic constraints played a substantial role and that the context issues act differently by employment type if reemployed. The results highlight the importance of socio-structural issues, reflecting resource asymmetry. Supportive neighborhoods and material deprivation set the scene, while education enables the pursuit of more stable and secure employment opportunities.
Social Sciences
Keywords: Labour market